Treating Cancer Cachexia Should be Essential in Cancer Care - Zhang, Lingbing; Bonomi, Philip D. (Archives of Clinical and Biomedical Research, 2025)
Cancer cachexia manifests as a multifaceted syndrome characterized by weight loss, appetite loss, muscle wasting, fatigue, weakness, and systemic disturbances, affecting patients’ physical function quality of life (QoL). Despite these negative effects, treatments have often been limited to supportive care with primary objective of symptom relief. This review aims to advocate for a reassessment of the clinical significance of effective therapies for cancer cachexia, positioning it as ‘essential’ care directed at the root cause of cachexia rather than ‘supportive’ care only. Essential care encompasses routine screening for cachexia using criteria such as the Global Leadership Initiative on Malnutrition (GLIM) or the Cachexia Score (CASCO), and therapeutic approaches that identify and inhibit mechanisms that are driving cachexia. Managing this multifactorial syndrome has involved a multimodal approach that has included non-steroidal anti-inflammatory drugs, nutritional support, physical activity, appetite-stimulating agents, and specific androgen receptor modulators. These approaches have not been successful. Instead, identifying drugs and biologics that are immunomodulators targeting the molecular and cellular immune dysfunction promoting cachexia is a strategy that could reduce symptoms and improve outcomes in cachectic cancer patients.